Fate of Zinc Oxide Nanoparticles Coated onto Macronutrient Fertilizers in an Alkaline Calcareous Soil - Milani, N.; Hettiarachchi, Ganga M.; Kirby, J. K.; Beak, D. G.; Stacey, S. P.; McLaughlin, M. J. (My University, 2015)
Zinc oxide (ZnO) nanoparticles may provide a more soluble and plant available source of Zn in Zn fertilizers due to their greater reactivity compared to equivalent micron-or millimetresized (bulk) particles. However, the effect of soil on solubility, spatial distribution and speciation of ZnO nanoparticles has not yet been investigated. In this study, we examined the diffusion and solid phase speciation of Zn in an alkaline calcareous soil following application of nanoparticulate and bulk ZnO coated fertilizer products (monoammonium phosphate (MAP) and urea) using laboratory-based x-ray techniques and synchrotron-based mu-x-ray fluorescence (mu-XRF) mapping and absorption fine structure spectroscopy (mu-XAFS). Mapping of the soil-fertilizer reaction zones revealed that most of the applied Zn for all treatments remained on the coated fertilizer granule or close to the point of application after five weeks of incubation in soil. Zinc precipitated mainly as scholzite (CaZn2(PO4)(2)center dot 2H(2)O) and zinc ammonium phosphate (Zn(NH4)PO4) species at the surface of MAP granules. These reactions reduced dissolution and diffusion of Zn from the MAP granules. Although Zn remained as zincite (ZnO) at the surface of urea granules, limited diffusion of Zn from ZnO-coated urea granules was also observed for both bulk and nanoparticulate ZnO treatments. This might be due to either the high pH of urea granules, which reduced solubility of Zn, or aggregation (due to high ionic strength) of released ZnO nanoparticles around the granule/point of application. The relative proportion of Zn(OH)(2) and ZnCO3 species increased for all Zn treatments with increasing distance from coated MAP and urea granules in the calcareous soil. When coated on macronutrient fertilizers, Zn from ZnO nanoparticles (without surface modifiers) was not more mobile or diffusible compared to bulk forms of ZnO. The results also suggest that risk associated with the presence of ZnO NPs in calcareous soils would be the same as bulk sources of ZnO.
Citation: Milani, N., Hettiarachchi, G. M., Kirby, J. K., Beak, D. G., Stacey, S. P., & McLaughlin, M. J. (2015). Fate of Zinc Oxide Nanoparticles Coated onto Macronutrient Fertilizers in an Alkaline Calcareous Soil. Plos One, 10(5), 16. doi:10.1371/journal.pone.0126275
Keywords: Zno Nanoparticles; Crop Response; Dissolution; Solubility; Speciation; Phosphate